The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ijms241411576
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Responsible for Diabetogenic Effects of COVID-19 Infection—Induction of Autoimmune Dysregulation and Metabolic Disturbances

Abstract: The COVID-19 pandemic has revealed a significant association between SARS-CoV-2 infection and diabetes, whereby individuals with diabetes are more susceptible to severe disease and higher mortality rates. Interestingly, recent findings suggest a reciprocal relationship between COVID-19 and diabetes, wherein COVID-19 may contribute to developing new-onset diabetes and worsen existing metabolic abnormalities. This narrative review aims to shed light on the intricate molecular mechanisms underlying the diabetogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 147 publications
0
1
0
Order By: Relevance
“…Nevertheless, some MR investigations have shown that there may not be a substantial correlation between T2D and the phenotype of COVID‐19 37,38 . In their review, Grubišić et al 39 proposed that COVID‐19 can potentially trigger the development of diabetes via the induction of immunological imbalance and glucose metabolism disruption. There exists a strong correlation between hyperglycemia and several factors, such as the duration of hospitalization, 40 the incidence of infection, 41 and the deterioration of patient outcomes 42 in individuals diagnosed with AP.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some MR investigations have shown that there may not be a substantial correlation between T2D and the phenotype of COVID‐19 37,38 . In their review, Grubišić et al 39 proposed that COVID‐19 can potentially trigger the development of diabetes via the induction of immunological imbalance and glucose metabolism disruption. There exists a strong correlation between hyperglycemia and several factors, such as the duration of hospitalization, 40 the incidence of infection, 41 and the deterioration of patient outcomes 42 in individuals diagnosed with AP.…”
Section: Discussionmentioning
confidence: 99%